DNA fingerprinting in assessment of genetic purity in rice - Tiwari, Jitendra Kumar; Tiwari, Ashish Kumar (Indian Farming, 2018)
The set of microsatellite and ISSR markers used here provides assessment of the ability of markers to produce unique DNA profile of rice genotypes. The data obtained can be used for varietal survey and the construction of a database of all rice varieties grown in Chhattisgarh. Molecular markers would enhance the standards of DUS testing, if they are included as additional descriptor. Seed-based techniques for varieties are warranted for rapid identification of seed lots. Therefore, in the present study, a strategy of using seed based chemicals tests for development of seed keys for rice varieties was demonstrated in four varieties developed by IGKV, Raipur. The SSR and ISSR markers can efficiently be used to generate locus specific allelic information which can serve as molecular IDs for four rice varieties namely, Karmamasuri, Danteshwari, Samleshwari and Mahamaya. Varietal fingerprints can be effectively used in assessment of seed purity in comparison to conventional GOT through saving on time, resource and energy. The cost effectiveness of marker based assay in testing genetic purity of rice varieties is one of the most important considerations while recommending the adoption of this technology the seed industry as an alternative to GOT. Besides being quick and accurate, the use of a single marker would be cost effective when compared to use of a combination of markers in testing genetic purity of seed samples.